The Hispano-Portuguese Cancioneiro of the Hispanic Society of America : Edition and Notes - Askins, Arthur Lee-Francis (University of North Carolina publications of the Department of Romance Languages., 2019)
This is a transcription of the previously unpublished seventeenth-century manuscript now in the possession of the Hispanic Society of America formerly known as the "Cancioneiro hispano-portugues da Academia das Ciencias, Lisboa." The volume is of importance to scholars of Spanish and Portuguese poetry of the Classical period, 1500-1700.